An Effectiveness Trial of an Exercise Physiologist Service to Improve Quality of Life in Adults with Severe Mental Illness: Protocol for the MOVEMENT Study [Corrigendum] - Chapman JJ; Siskind D; Yung AR; Lee YY; Arnautovska U; Scott JG; Burke K; Malacova E; Korman N; Wyder M; Doohan MA; Keating SE; et al. (Neuropsychiatric Disease and Treatment, 2025)
Chapman JJ, Siskind D, Yung AR, et al. Neuropsychiatr Dis Treat. 2025;21:1399–1408. The authors have advised that the funding statement on page 1406 is incorrect. The correct statement should read as follows. FundingThis work is funded by a grant from the Medical Research Futures Fund (App ID: 2023060). This work is also funded by contribution from the Brisbane North Primary Health Network. This work was supported by a grant from the Australian National Health and Medical Research Council Special Initiative in Mental Health 2021–2026 (GNT2002047). This article contains the opinions of the authors and does not in any way reflect the views of the National Health and Medical Research Council. The financial assistance provided must not be taken as endorsement of the contents of this paper. The authors apologize for this error.